An ultra-fast and eco-friendly recycling process for spent LIBs using deep eutectic solvents: mechanism and life-cycle insight - Liu,S; Li,S; Cao,XE; Choi,S (Green Chemistry, 2025)
The accumulation of end-of-life lithium-ion batteries (LIBs) highlights the need for an efficient and environmentally friendly recycling process. Deep eutectic solvents (DESs) have gained significant attention due to their benefits of being green and economical; however, the environmental impact of processes using DESs has not been widely studied yet. In this context, a rapid leaching method using a green choline chloride (ChCl)–maleic acid (MA) DES was applied to LIBs leaching, which showed much enhanced kinetics compared with most of the DESs and achieved high leaching efficiencies of 84.53% for Li and 80.04% for Co from LCO within 10 min at 140 °C. The ChCl–MA DES can serve both as a lixiviant and a reducing agent, with a reducing ability comparable to that of the traditional hydrometallurgy reductant H2O2. The ChCl–MA DES presented good reusability and adaptability which can be reused for 5 times with performance remained unchanged and suitable for multiple LIBs include LMO, LFP and NMC. Through density functional theory (DFT) calculations, the leaching mechanism was analyzed: the carboxyl group of MA reduced Co(iii) to Co(ii), making it soluble, and Cl− within the DES formed stable [LiCl2]− and [CoCl4]2− complexes with Li and Co, respectively. Moreover, based on a life cycle assessment (LCA), the environmental impact of the DES leaching process was assessed and it was validated as being effective and eco-friendly for recycling spent LIBs, compared with an ethylene glycol DES, a urea DES, and the same DES with different molar ratios. This study eliminated the use of corrosive acids and mitigated the typically severe conditions of DES leaching, offering a practical approach for recovering spent LIBs.